Kinerja pasar ASEAN-5 selama isu krisis global - Yulianti, Stevia Della; Mokoginta, Isti Julisti; Lapure, Magdalena Grace (Yayasan Widyantara Nawasena Raharja, 2024)
The issue of the global crisis in early 2023 will have quite an impact on world economic conditions, especially in countries that are members of ASEAN-5. The findings show that the Malaysian and Thai markets tend to have quite significant index declines throughout the observation period. This study also shows that the Malaysian and Thai markets are indicated to have low risk throughout early 2023. The findings of this study imply that markets in ASEAN-5 have a unidirectional relationship throughout the observation period in early 2023. However, the findings of this study also show that the Indonesian market only has a significant relationship with the Malaysian market compared to other ASEAN-5 markets. Throughout global issues in early 2023, increases or decreases in market indices in ASEAN-5 tend not to differ significantly.